(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Civil engineers know that fatigue indicates the majority of structural failures. In plain and reinforced concrete structures, fatigue might account for excessive deformation, excessive of crack widths, de-bonding of reinforcement and rupture of the reinforcement, all of these can lead to structural collapse. Fatigue crack propagation can be a method to predict a remaining life of structures. Herein some works that have been done will be shown in order to analyse the fatigue crack growth for plain concrete specimens. The goals of this study are to estimate the critical crack length and remaining life of a plain concrete specimen, determine the state of the specimen either having failed or being safe using first order reliability method (FORM) and assess which parameter has most influence on the reliability index